First report on the pollination of Neotinea maculata (Orchidaceae) by minor worker ants of the Temnothorax exilis group (Hymenoptera: Formicidae) - García-Gila, Jaime; Blasco-Aróstegui, Javier (Mediterranean Botany, 2021)
Ants commonly visit flowers seeking for food resources such as nectar. However, only eight species of orchids are known for having an effective pollinaria removal by ants. In this study, the visit of the orchid Neotinea maculata (Desf.) Stearn by ants is described in one of the three known populations from the province of Valladolid (Spain). Through direct observation, six minor worker ants of Temnothorax exilis (Emery, 1869) (Hymenoptera: Formicidae) group were found visiting flowers of six plants of N. maculata, and four of them were carrying pollinaria on their heads. Other insects were not observed with pollinaria or visiting the flowers. Overall, we found that 33.3% of all the flowers had no pollinaria (96 flowers without pollinaria in a total of 288 flowers). Nevertheless, despite ants observed in the field only promoted cross-pollination between flowers of the same individual (geitonogamy), there is a possibility that the ant will visit another plant’s inflorescence. Thus, ants could be considered not only as visitors but also as true pollinators of N. maculata.